Metal-ligand dual-site single-atom nanozyme mimicking urate oxidase with high substrates specificity - Wang, Kaiyuan; Hong, Qing; Zhu, Caixia; Xu, Yuan; Li, Wang; Wang, Ying; Chen, Wenhao; Gu, Xiang; Chen, Xinghua; Fang, Yanfeng; Shen, Yanfei; Liu, Songqin; et al. (Nature communications, 2024)
In nature, coenzyme-independent oxidases have evolved in selective catalysis using isolated substrate-binding pockets. Single-atom nanozymes (SAzymes), an emerging type of non-protein artificial enzymes, are promising to simulate enzyme active centers, but owing to the lack of recognition sites, realizing substrate specificity is a formidable task. Here we report a metal-ligand dual-site SAzyme (Ni-DAB) that exhibited selectivity in uric acid (UA) oxidation. Ni-DAB mimics the dual-site catalytic mechanism of urate oxidase, in which the Ni metal center and the C atom in the ligand serve as the specific UA and O 2 binding sites, respectively, characterized by synchrotron soft X-ray absorption spectroscopy, in situ near ambient pressure X-ray photoelectron spectroscopy, and isotope labeling. The theoretical calculations reveal the high catalytic specificity is derived from not only the delicate interaction between UA and the Ni center but also the complementary oxygen reduction at the beta C site in the ligand. As a potential application, a Ni-DAB-based biofuel cell using human urine is constructed. This work unlocks an approach of enzyme-like isolated dual sites in boosting the selectivity of non-protein artificial enzymes. Single-atom nanozymes are a type of non-protein artificial enzymes and promising for mimicking enzyme active centers, but lack recognition sites to confer substrate specificity. Here, the authors report on a metal-ligand dual-site single-atom nanozyme (Ni-DAB) that mimics the dual-site catalytic mechanism of urate oxidase and has high selectivity in uric acid (UA) oxidation.